A Method for Membrane Characterization Employing Reliable Forward Osmosis Experimental Data - Reyes Lombardo, Sofia (Université d'Ottawa / University of Ottawa, 2021)
Forward osmosis (FO) is an osmotically driven process that uses a high concentration draw solution to pull water across a semipermeable membrane from a feed solution. Wastewater, seawater, or other contaminated water sources may be used as a feed solution. In FO, the final product is not clean water but a diluted draw solution. However, FO may be combined with another process, e.g. reverse osmosis (RO). The resulting hybrid process offers advantages compared to the RO process in, for example, seawater desalination. Thin-film composite (TFC) membranes have been used in pressurized processes such as RO due to their thick porous support layer and their ability to endure high hydrostatic pressures. However, the presence of a thick porous layer is detrimental for FO processes. It is responsible for the internal concentration polarization (ICP) inside the membrane, reducing the osmotic driving force and the overall water flux. The characterization of membranes in FO applications is key for understanding how different intrinsic parameters affect membrane performance. In this work, a previously developed methodology for characterizing TFC membranes was improved. Experimental data was obtained from a laboratory-scale FO system, and the experimental data was used to determine three intrinsic transport parameters, namely the water permeance, the salt permeance and the porous layer structural parameter. With this method, the characterization of TFC membranes can be achieved based exclusively on FO data. A sensitivity analysis has highlighted the impact of the intrinsic transport parameters on an FO membrane performance.
Keywords: Forward Osmosis; Membrane Characterization